THE USE OF STUDENT CENTERED LEARNING IN TEACHING PROCESS TO HELP STUDENTS COMPREHEND THEIR READING SKILL - Herliyana Budi Almandayanti; Kurniawan Budhi Nugroho (Jurnal Ilmiah Sultan Agung, 2023)
Many facets of life have advanced quickly in this age of globalization, including education. The government has implemented a student-centered learning policy, also known as learning in a new paradigm, in an effort to produce a generation that is capable of becoming independent. Many schools in Indonesia have begun using student-centered learning as a teaching strategy, especially for English language instruction. Reading literature written in English presents challenges for many students. Students will not comprehend what they are studying as a result of these issues. The goal of this study is to ascertain whether a student centered learning of teaching techniques can be used to help students appreciate their reading abilities while learning English and to ascertain the impact of doing so. The instruments employed in this study's qualitative study in action research were interviews, observations, rubrics, and portfolios. Participants in the study were the English teacher and students in grade X TKJ 1. The author served as a tutor for the duration of the study. According to the findings, students' reading comprehension can be enhanced by the student centered learning method to teaching English. Keywords: Student centered learning; teaching process; reading comprehension